"I know what I want but I'm not sure how to get it"—Expectations of physiotherapy treatment of persons with persistent pain. (4th March 2017) - Calner, Tommy; Isaksson, Gunilla; Michaelson, Peter
ABSTRACT: Expectations of physiotherapy treatment of patients with persistent pain have been shown to influence treatment outcome and patient satisfaction, yet this is mostly explored and described in retrospective. The aim of the study was to explore and describe the expectations people with persistent pain have prior to physiotherapy treatment. Ten participants with persistent musculoskeletal pain from the back, neck, or shoulders were included in the study. Data were collected by interviews using a semi-structured interview guide and were analyzed with qualitative content analysis. The analysis resulted in one main category: "The multifaceted picture of expectations" and four categories: 1) Standing in the doorway: curious and uncertain; 2) Looking for respect, confirmation and knowledge; 3) Expecting treatment, regular training, and follow up; and 4) Having dreams, being realistic, or feeling resigned. The main category and the categories describe a multifaceted picture of the participants' expectations, gradually developed and eventually encompassing several aspects: good dialog and communication, the need to be confirmed as individuals, and getting an explanation for the pain. The results also show that the participants expected tailored training with frequent follow-ups and their expectations of outcome ranged from hope of the best possible results to realistic or resigned regarding pain relief and activity levels.